Infection prevention and control across the continuum of COVID‐19 care: A qualitative study of patients', caregivers' and providers' experiences. (12th July 2022) - Wasilewski, Marina B.; Szigeti, Zara; Sheppard, Christine L.; Minezes, Jacqueline; Hitzig, Sander L.; Mayo, Amanda L.; Robinson, Lawrence R.; Lung, Maria; Simpson, Robert
Abstract: Introduction: Healthcare facilities adopted restrictive visitor policies as a result of the COVID‐19 (COVID) pandemic. Though these measures were necessary to promote the safety of patients, families and healthcare providers, it led to isolation and loneliness amongst acute care inpatients that can undermine patient rehabilitation and recovery. The study objectives were to (1) explore how infection prevention and control (IP&C) measures impacted stakeholders' perceptions of care quality and interactions with others and (2) investigate how these experiences and perceptions varied across stakeholder groups and care settings. Methods: A qualitative descriptive study was conducted. Patients and their families from an inpatient COVID rehabilitation hospital and healthcare providers from an acute or rehabilitation COVID hospital were interviewed between August 2020 and February 2021. Results: A total of 10 patients, 5 family members and 12 healthcare providers were interviewed. Four major themes were identified: (1) IP&C measures challenged the psychosocial health of all stakeholders across care settings; (2): IP&C measures precipitated a need for greater relational care from HCPs; (3) infection prevention tenets perpetuated COVID‐related stigma that stakeholders experienced across care settings; and (4) technology was used to facilitate human connection when IP&C limited physical presence. Conclusion: IP&C measures challenged psychosocial health and maintenance of vital human connections. Loneliness and isolation were felt by all stakeholders due to physical distancing and COVID‐related stigma. Some isolation was mitigated by the relational care provided by HCPs and technological innovations used. The findings of the study underscore the need to balance safety with psychosocial well‐being across care settings and beyond the patient–provider dyad. Patient and Public Contribution: This study was informed by the Patient‐Oriented Research Agenda and developed through consultations with patients and family caregivers to identify priority areas for rehabilitation research. Priority areas identified that informed the current study were (1) the need to focus on the psychosocial aspects of recovery from illness and injury and (2) the importance of exploring patients' recovery experiences and needs across the continuum of care. The study protocol, ethics submission, analysis and manuscript preparation were all informed by healthcare providers with lived experience of working in COVID care settings.